2017
DOI: 10.1097/pgp.0000000000000346
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Carcinosarcomas: Clinical, Histopathologic and Immunohistochemical Characteristics

Abstract: Carcinosarcomas (malignant mixed Müllerian tumors or MMMT) are rare malignant tumors in the female genital tract composed of both malignant epithelial and malignant mesenchymal components. They comprise <5% of all neoplasms in the gynecologic tract and have an aggressive clinical course. The purpose of this study is to evaluate the immunophenotype and possible histogenesis of carcinosarcomas of the uterus. Sixty-two cases of uterine carcinosarcomas diagnosed between 1995 and 2011 were retrieved from the gyneco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…The fact of dualistic nature of carcinosarcomas (Chen et al 2017) combined with revealed in this research fucoidan influence on cell viability, apoptosis as well as cell cycle arrest in carcinosarcoma cell lines may suggest fucoidan’s potential activity against endometrial cancer cells.…”
Section: Discussionmentioning
confidence: 52%
“…The fact of dualistic nature of carcinosarcomas (Chen et al 2017) combined with revealed in this research fucoidan influence on cell viability, apoptosis as well as cell cycle arrest in carcinosarcoma cell lines may suggest fucoidan’s potential activity against endometrial cancer cells.…”
Section: Discussionmentioning
confidence: 52%
“…6 CSs are composed of high-grade carcinomatous and sarcomatous elements often with a sharp demarcation between the 2. Heterologous elements most commonly rhabdomyosarcoma, but also chondrosarcoma, osteosarcoma, or rarely liposarcoma may be identified, 35,36 whereas CHEC/ECS lack malignant heterologous components although osseous metaplasia is enigmatically common in CHEC. 3,4 The key morphologic features that favor a diagnosis of CHEC or ECS over CS include conventional EC merging with the corded and hyalinized and spindle cell components, both typically lacking high-grade cytologic atypia.…”
Section: Figure 3 Ec With Spindle Cells Low-grade Spindle Cells Formi...mentioning
confidence: 99%
“…The mesenchymal component can be “homologous” with types of differentiation native to the uterus, such as smooth muscle or endometrial stroma. Remarkably, however, the mesenchymal component is conspicuously “heterologous” in half of cases, exhibiting, for example, obvious cartilaginous or osseous differentiation (chondrosarcoma or osteosarcoma) (5).…”
mentioning
confidence: 99%